Ski binding performance, biomechanics, testing, and engineering design - Brown, C. A. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: A rigorous, science-based, engineering design method is used to explain how ski bindings can protect ACLs and avoid inadvertent release. Additionally, it shows how appropriate binding retention/release setting methods could be developed for elite skiers. In skiing, as other sports, awareness of injury mechanisms and how they can be avoided has not led to safer equipment. For decades concepts for ski bindings that could reduce ACL injuries and inadvertent release have been patented, presented, and published [1,2]. Yet, equipment designs from most manufacturers still do not address these problems. ACL injuries continue at unfortunately high rates. Inadvertent release problems are addressed by increasing release settings and increasing injury risks. Sports science and sports medicine communities could foster more innovation by promoting publication and presentation of design work. This could encourage dialog, activity, and investment required to develop and realize design innovations.